2017
DOI: 10.1177/0021998317705705
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel high Tg polyimide-based composites. Part I: RTM processing properties

Abstract: In this study, an assessment of the composite processing-related properties of a newly developed 6-FDA-based phenylethynyl-terminated polyimide (available under the tradename NEXIMID Õ MHT-R) is presented. Processing schemes, used for preparing high quality carbon fibre-reinforced composites by the use of conventional resin transfer moulding are developed and presented. The influences of manufacturing parameters on glass transition temperature of the composites are presented. The results confirm that composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…After cured at 343 °C for 8 h, the T g of the formulation based on a-BTDA and 3,3′-diaminobenzophenone (3,3′-DABP) exceeded 400 °C. Furthermore, in order to improve the heat resistance of PETI, Fernberg et al [ 30 ] introduced ethynyl moiety into the main chain of phenylethynyl end-capped polyimide resins that are amenable to RTM, by using ethynyl bis-phthalic anhydride (EBPA). During cure at 370 °C and post-cure at a temperature of over 400 °C, the T g of materials could reach 400 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After cured at 343 °C for 8 h, the T g of the formulation based on a-BTDA and 3,3′-diaminobenzophenone (3,3′-DABP) exceeded 400 °C. Furthermore, in order to improve the heat resistance of PETI, Fernberg et al [ 30 ] introduced ethynyl moiety into the main chain of phenylethynyl end-capped polyimide resins that are amenable to RTM, by using ethynyl bis-phthalic anhydride (EBPA). During cure at 370 °C and post-cure at a temperature of over 400 °C, the T g of materials could reach 400 °C.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our best knowledge, there are little reports on its causes and effect factors. Usually, the viscosity of resins increases over time under isothermal conditions, which was considered to be induced by the curing of phenylethynyl groups [ 28 , 30 ]. Scola et al [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…T g is the temperature at which the macromolecular components of the polymer begin to move. 18 When the temperature is below T g , the molecular chains of the polymeric materials are frozen in a glass state allowing the polymers to have numerous practical uses. By contrast, the glass state morphology of polymeric materials will be converted to a rubbery state when the temperature is above T g .…”
Section: Glass Transition Behaviormentioning
confidence: 99%
“…Additionally, the introduction of a second crosslinkable segment in the main chain of thermosetting polyimide, besides the PEPA crosslinking agent, has also been studied in order to further improve the heat resistance of polyimide resins and maintain simultaneously the melt processability of its oligoimides. Fernberg et al developed a 6FDA-based phenylethynyl-terminated polyimide resin MHT-R suitable for RTM by introducing ethynyl bis-phthalic anhydride (EBPA) into the main chain [ 17 , 18 ]. They found that MHT-R resin exhibited relatively low melt viscosity of 0.2–2.0 Pa·s between 250–320 °C, which is suitable for fabricating high-quality carbon fiber-reinforced composites by RTM.…”
Section: Introductionmentioning
confidence: 99%